Analysis of subsynchronous current propagation path of subsynchronous oscillation induced by renewable energy integrated to the power grid. Issue 13 (19th December 2017) - Zhang, Peng; Xu, Puxuan; Bi, Tianshu
Abstract : This paper deals with operational parameter to study the propagation path of the subsynchronous current generated by the wind farm. First, the complex frequency domain operation parameter model of the transmission network, thermal power generator and other power system components are established. Then, the wind farm is taken as the subsynchronous current injection point and the subsynchronous current's propagation path is analysed according to the frequency impedance characteristic of the transmission network. The influences of the current frequency, the position of the wind farms and the structure of the AC system on the harmonic current distribution are analysed and studied with this method. Then the digital simulation method is used to demonstrate the conclusion drawn from the theoretical method. On the basis of the method proposed, the subsynchronous component shunt coefficient of the power system actual operation can be obtained initially.